Dampak Kerusakan Jalan Terhadap Lalu Lintas Pada Ruas Jalan Timor Raya KM 28, Kupang - Adoe, Putri Angelia; Bolla, Margareth Evelyn; Nasjono, Judi K; Lau, Debora; Amalo, Patricia Sonia (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2025)
The road is an important land transportation infrastructure, so a good pavement design is a must because poor road conditions can affect traffic performance. This study aims to determine the impact of road damage on traffic on the Timor Raya road segment Km 28, Oesao, Kupang Regency. Road damage analysis was conducted using the PCI method on three road segments, and traffic analysis used the PKJI 2023 method. The research results show the of road damage in segment I: 69.1 (Fair), segment II: 86,2 (Good), and segment III: 94,1 (Good). Vehicle volume during peak hours was segment I: 1641.4 smp/jam, segment II: 1510.4 smp/jam, and segment III: 1076.3 smp/jam. Side friction during peak hours was segment I: 975.6 kej/jam, segment II: 591.4 kej/jam, and segment III: 1056.4 kej/jam. Vehicle speed on a good road was segment I: 46 km/jam, segment II: 44 km/ jam, and segment III: 45 km/ jam. Vehicle speed on a damaged road was segment I: 37 km/ jam, segment II: 36 km/ jam, and segment III: 44 km/ jam. The impact on traffic is that it can cause congestion at points of damage and affect vehicle speed.